2004
DOI: 10.1246/cl.2004.1468
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 3-Aminopropyltriethoxysilane-Modified Superparamagnetic Magnetite Nanoparticles

Abstract: The aminosilane-modified magnetite nanoparticles were synthesized by the coprecipitation and surface modification with 3-aminopropyltriethoxysilane (APTTS). The superparamagnetic APTTS/Fe3O4 nanospheres with an average diameter of 10 nm were characterized significantly with functional group, well dispersion and stabilization in aqueous fluids, as well as a maximized saturation magnetization of 63.54 emu/g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(77 citation statements)
references
References 12 publications
7
62
3
2
Order By: Relevance
“…Secondly, the black magnetite particles were covered with silica based on the Stöber method [19]: the black magnetite was ultrasonically dispersed into a mixture of ethanol-water solution, NH 4 OH and TEOS, and the mixture was stirred for 6 h to produce the core-shell structured Fe 3 O 4 @SiO 2 which was collected with an external magnet and washed sequentially with water and ethanol. Thirdly, the Fe 3 O 4 @SiO 2 was redispersed into 150 mL ethanol/water (v:v, 1:1) solution, and stirred with 200 μL of APTMS under N 2 protection at 40°C for 8 h to introduce amine groups on the surface of Fe 3 O 4 @SiO 2 [20]. Finally, the aminomodified particles Fe 3 O 4 @SiO 2 -NH 2 were stirred with 10% succinic anhydride in DMF solution under nitrogen atmosphere for 3 h at room temperature, to obtain the final carboxyl-modified magnetic nanoparticles Fe 3 O 4 @SiO 2 -NH 2 -COOH, which after centrifugation and washing with water, were dried under vacuum at 40°C [21].…”
Section: Preparation and Characterization Of Magnetic Nanoparticles Cmentioning
confidence: 99%
“…Secondly, the black magnetite particles were covered with silica based on the Stöber method [19]: the black magnetite was ultrasonically dispersed into a mixture of ethanol-water solution, NH 4 OH and TEOS, and the mixture was stirred for 6 h to produce the core-shell structured Fe 3 O 4 @SiO 2 which was collected with an external magnet and washed sequentially with water and ethanol. Thirdly, the Fe 3 O 4 @SiO 2 was redispersed into 150 mL ethanol/water (v:v, 1:1) solution, and stirred with 200 μL of APTMS under N 2 protection at 40°C for 8 h to introduce amine groups on the surface of Fe 3 O 4 @SiO 2 [20]. Finally, the aminomodified particles Fe 3 O 4 @SiO 2 -NH 2 were stirred with 10% succinic anhydride in DMF solution under nitrogen atmosphere for 3 h at room temperature, to obtain the final carboxyl-modified magnetic nanoparticles Fe 3 O 4 @SiO 2 -NH 2 -COOH, which after centrifugation and washing with water, were dried under vacuum at 40°C [21].…”
Section: Preparation and Characterization Of Magnetic Nanoparticles Cmentioning
confidence: 99%
“…In the spectra of ε eff for Fe-doped silica film the maximum was revealed at 2.3 and 2.7 eV for samples grown from precursors with and without APTES, respectively. This difference could be caused by the surface modification of Fe-containing nanoparticles [4].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, nanoparticles of transition metals were synthesized and intensively studied [1][2][3][4]. It was found that various nanoparticles of transition metals and their oxides were formed depending on technological procedure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations